Access 2013 : the missing manual - MacDonald, Matthew (Missing manual., 2013)
Unlock the secrets of Access 2013 and discover how to use your data in creative ways. With this book's easy step-by-step instructions, you'll learn how to build and maintain a full-featured database and even turn it into a web app. You also get tips and practices from the pros for good database design--ideal whether you're using Access for business, school, or at home. The important stuff you need to know Build a database with ease. Organize and update lists, documents, catalogs, and other types of information. Create your own web app. Let your whole team work on a database in the cloud. Share your database on a network. Link your Access database to SQL Server or SharePoint. Customize the interface. Make data entry a breeze by building your own templates Find what you need fast. Search, sort, and summarize huge amounts of data in minutes. Put your info to use. Turn raw info into well-formatted printed reports. Dive into Access programming. Automate complex tasks and solve common challenges.